Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd003577.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and materials for skin closure in caesarean section

Abstract: Editorial group: Cochrane Pregnancy and Childbirth Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 9, 2012. Review content assessed as up-to-date: 30 June 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…10,11 In the present study, apposition of the epidermal margins along the sutured incision was assessed as a predictor of scar formation. We suspect that skin apposition is positively correlated with cosmesis, but that can be only confirmed with an in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In the present study, apposition of the epidermal margins along the sutured incision was assessed as a predictor of scar formation. We suspect that skin apposition is positively correlated with cosmesis, but that can be only confirmed with an in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…Clay FS, Walsh CA (13) found wound separation (pooled odds ratio, 4.01; P < .0001) and composite wound complication (pooled odds ratio, 2.11; P = .003) rates were higher with staples. Mackeen AD (14) , Agbakwuru EA (15) ,Lundbald R (16) , MR. A Subramanian (6) , and Eldrup (17) et.al. found no difference in postoperative infection rates using staples or sutures.…”
Section: Wound Infection Ratesmentioning
confidence: 99%
“…A systematic review identified eight RCTs evaluating these three alternatives for closure of the Pfannenstiel incision in the general CS population, and found similar incidences of wound complications with staples and subcuticular sutures, as well as similar pain and cosmetic results [40]. Staple removal before the fourth post-operative day was associated with an increased risk of skin separation.…”
Section: Closure Of the Skinmentioning
confidence: 99%